СОВМЕСТНАЯ НАУЧНАЯ ДЕЯТЕЛЬНОСТЬ РОССИЙСКИХ И БЕЛОРУССКИХ УЧЕНЫХ: ТЕКУЩЕЕ СОСТОЯНИЕ И ТЕНДЕНЦИИ РАЗВИТИЯ (Библиосфера)
The article represents bibliometric analysis of current status and developmental tendencies in Russian-Belorussian scientific collaboration during the last ten years by different parameters: dynamic characteristics of publication activity, citation index, average and cumulative impact-factor, participation of Funds providing financial support of scientific research.